Experimental Study on Bond Behavior between Plain Reinforcing Bars and Concrete - Guohua Xing; Cheng Zhou; Tao Wu; Boquan Liu (Advances in Materials Science and Engineering, 2015)
To evaluate the bond behavior between the reinforcing bar and surrounding concrete, a total of six-group pullout specimens with plain steel bars and two-group specimens with deformed steel bars, serving as a reference, are experimentally investigated and presented in this study. The main test parameters of this investigation include embedment length, surface type of reinforcing bars, and bar diameter. In particular, the bond mechanism of plain steel reinforcing bars against the surrounding concrete was analyzed by comparing with six-group pullout specimens with aluminium alloy bars. The results indicated that the bond stress experienced by plain bars is quite lower than that of the deformed bars given equal structural characteristics and details. Averagely, plain bars appeared to develop only 18.3% of the bond stress of deformed bars. Differing from the bond strength of plain steel bars, which is based primarily on chemical adhesion and friction force, the bond stress of aluminium alloy bars is mainly experienced by chemical adhesion and about 0.21~0.56 MPa, which is just one-tenth of that of plain steel bars. Based on the test results, a bond-slip model at the interface between concrete and plain bars is put forward.